2021
DOI: 10.1039/d1ra02365a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structures, and catalytic efficiency in ring opening polymerization of rac-lactide with tridentate vs. bidentate cobalt(ii), zinc(ii), and cadmium(ii) complexes containing N-substituted N,N-bis((3,5-dimethyl-1H-pyrazol-1-yl)methyl)amine ligands

Abstract: Co(ii), Zn(ii), and Cd(ii) complexes supported by bis-pyrazolyl ligands were applied to the ring-opening polymerization of rac-lactide to produce heterotactic polylactides (PLAs) with superior heterotactic bias i.e. Pr up to 0.94 at −25 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 89 publications
2
10
0
Order By: Relevance
“…However, further increase in the [ rac -LA] 0 /[catalyst] ratio up to 700:1 resulted in only 31% conversion under identical experimental protocols, and a decrease in the molecular weight of resultant PLA was also observed with this decrease in conversion (Figure ). Depending on the metal center variation, [L TH ZnCl 2 ]/LiO i Pr resulted in a high heterotactic enchainment ( P r = 0.74 at 0 °C) compared to its Cd­(II) and Pd­(II) complexes, consistent with the findings of previous studies. , Decrease in polymerization temperature did not show any significant enhancement of the heterotactic bias, particularly for the Cd­(II)-based initiator. The geometry of the M­(II) complex might have steered the hetereotacticity of PLA in the studied complexes.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, further increase in the [ rac -LA] 0 /[catalyst] ratio up to 700:1 resulted in only 31% conversion under identical experimental protocols, and a decrease in the molecular weight of resultant PLA was also observed with this decrease in conversion (Figure ). Depending on the metal center variation, [L TH ZnCl 2 ]/LiO i Pr resulted in a high heterotactic enchainment ( P r = 0.74 at 0 °C) compared to its Cd­(II) and Pd­(II) complexes, consistent with the findings of previous studies. , Decrease in polymerization temperature did not show any significant enhancement of the heterotactic bias, particularly for the Cd­(II)-based initiator. The geometry of the M­(II) complex might have steered the hetereotacticity of PLA in the studied complexes.…”
Section: Resultssupporting
confidence: 89%
“…This might be due to the rigidity of the 4-(quinolin-2-ylmethyl)­morpholine ligand framework compared to L TH . As it was shown earlier, , the rac -LA ROP proceeds through a monomer-activated mechanism initiated by diispropoxide-based Zn­(II) species. It was shown that for rac -LA polymerization, the studied catalytic system outperforms the Zn­(II) complexes of tridentate Schiff bases with morpholine/piperidine/pyridine/quinoline functionalities for rac -LA polymerization with better conversion and polymerization control of PLA production.…”
Section: Resultsmentioning
confidence: 61%
“…The N imine -M-N amine and N pyridine -M-N amine bond angles signifies trigonal bipyramidal and square pyramidal geometries for these complexes. 8,[65][66][67]69 The Cl terminal -M-Cl terminal bond angles in [DEP(Cu) Cl 2 ] and [DEP(Zn)Cl 2 ] were 103.12(4) and 117.87 (19) , respectively, whereas the…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…10 Recent advancements in developing efficient stereoselective catalysts are based on late transition metal initiators with different ancillary ligands toward the ROP of rac-LAs. [11][12][13][14][15][16] We recently established the role of the initiating groups, namely, LiMe, LiO i Pr, and LiCl, based on their basicity, for Zn(II) complexes in a controlled ROP of rac-LA. 17 In our previous studies on LA polymerization, we focused on the LiMe system.…”
Section: Introductionmentioning
confidence: 99%
“…17 In our previous studies on LA polymerization, we focused on the LiMe system. 11,12,16 Here, we discuss the impact of the initiating groups, LiMe and LiO i Pr on the ROP properties of Co(II) and Cu(II) complexes containing an Jaegyeong Lee and Saira Nayab contributed equally to this article. aminomethylquinoline (L) ligand.…”
Section: Introductionmentioning
confidence: 99%